A Study Of Teaching English Speaking At Senior High School In Bima - Wahyuddin Wahyuddin (STKIP Harapan Bima, 2021)
The objective of this study is to describe the teaching of English Speaking AT Senior High School (SMA) 2 Woha-Bima. This study is naturalistic case study were the researcher must stand-by at the school to getting and collected the data. The method of collecting data is observation, interview and documentation. The result shows that the curriculum of teaching English is tries to use Cambridge curriculum and K13 Curriculum . The materials of the English teaching are taken form textbook, internet, and the other resources which related to the materials. The teacher activities in the classroom are; pre-activities, main-activities and post-activities. Besides, the teacher’s check student’s assignment and control them. Then, the methods of teaching English are communicative approaches, group discussion, speaking practice, and English club. The teacher is teaching the students dominated used English. Both of teacher and students are active in the classroom. For the assessing students by give the oral and written test. The teacher give the values is very objectives, it means the scores depend on student’s ability to finished the assignment or testing.